Serenade for string trio in D major, op. 8, published by Artaria (ca. 1820) - Beethoven, Ludwig van, 1770-1827 (composer)::::::::::::::: (Artaria e comp.; Austria; Vienna, 2024)
Early edition of the Serenade in D major for violin, viola, and cello, op. 8, later issue of the first edition originally published by Artaria in 1797.